Reply to May and Spottiswoode's "The Global Consciousness Project: Identifying the Source of Psi" - Bancel, Peter (Journal of Scientific Exploration, 2011)
I am pleased that May and Spottiswoode have initiated a discussion about the Global Consciousness Project (GCP), and I would like to thank the JSE editors for this opportunity to respond to their paper. May and Spottiswoode (M&S) suggest that the source of the statistical deviations reported by the GCP can be attributed to an experimenter effect and that Decision Augmentation Theory (DAT) can adequately model the GCP results. While I disagree with the analysis, their contribution is particularly welcome since they address an essential question that needs to be resolved by any model: Does the GCP measure a real, physical effect?